Can bone-specific alkaline phosphatase be a marker of vascular calcification in type 2 diabetes mellitus? - Nishant Raizada; Mohammad Aslam; B K Mishra; Diwesh Chawla; S V Madhu (Indian Journal of Endocrinology and Metabolism, 2023)
Background and Aims: Alkaline phosphatase (ALP) enzyme has been linked to vascular calcification. Unexplained elevations in serum ALP levels have been reported in patients with type 2 diabetes mellitus (T2DM). We assessed bone-specific alkaline phosphatase (BAP) levels in patients with T2DM who had unexplained ALP elevations and studied the association between BAP and other markers of vascular calcification. Methods: Patients with T2DM who had high serum ALP in the absence of known causes of ALP elevation were studied. The control group was T2DM patients with normal ALP. We measured the serum levels of BAP along with the leptin, fetuin-A, and vitamin K2 levels. Ankle–brachial index (ABI) was also measured in both groups. Results: Serum BAP levels were significantly higher in the group with high ALP when compared with the normal ALP group. A significant positive correlation was present between BAP and serum fetuin-A as well as between BAP and Vit K2 levels. There was no correlation between BAP and serum leptin. ABI was comparable between the two groups. Conclusions: Patients with T2DM may have unexplained elevation in ALP due to an increase in BAP. Elevation in BAP may be associated with other markers of vascular calcification suggesting an increased risk of vascular calcification.